Penerapan Senam Lansia dalam Upaya Menurunkan Nyeri Sendi Lutut pada Lansia di Puskesmas Gemolong - Mindar Endang Wahyuni; Anjar Nurrohmah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Background : An elderly person is someone over 60 years old who experiences changes, one of which is changes in musculoskeletal disorders. Joint pain is a symptom that disturbs the joints due to reduced synovial fluid so that the bones rub against the lining between the joints. Joint pain sufferers in Indonesia reach 81% of the 80 million elderly. Treatment for joint pain is done with non-pharmacological treatment, one of which can be done with non-pharmacological therapy is Elderly Gymnastics. Objective : To determine changes in the pain scale in the elderly before and after doing elderly exercise. Method : This research is a case study research using descriptive methods, namely by interviewing 2 (two) elderly respondents who experienced joint pain before and after implementing elderly exercise 3 times a week every morning. The instrument used was the Numerical Rating Scale (NRS) to measure delivery pain. Results : Before doing elderly exercise, both respondents experienced right and left knee pain on a scale of 4 (moderate pain) and scale 1 (mild pain). After doing elderly exercise for both respondents, there was a decrease in the pain scale with a scale of 1 (mild pain). Conclusion : This application shows that after implementing elderly exercise for both respondents, there was a reduction in joint pain in the elderly.